The Supply Chain Improvement Planning and Supply Chain Performance: Does the Global Configuration of Supply Chain Matters in Thai Based International Firms? - Laosillapacharoen, Khomsan; Aeknarajindawat, Natnaporn; Charoen-Rajapark, Norawat; Boonaram, Teepakorn (International Journal of Supply Chain Management, 2020)
The study, which is carried out on the Thai international firms, is investigating the impact of supply chain improvement planning on the supply chain performance. In addition to that, the study has examined the mediating role of the global configuration of the supply chain. The sample size in this study has been selected of 375, which is considered suitable and acceptable. The stratified random sampling design was used in the research. The population is divided into subgroups or strata from where random samples are drawn from each of the created strata in proportion to the entire population. The SEM-PLS has used to analyze the data. The findings of the study have shown agreement with the proposed hypothesis.Â  The findings of the study have revealed the fact that there is a need for the companies to focus on the investment areas and deal with the global SC configuration adopted by them. Along with the findings has broached that there is a variation of results from one group to another. Locals can achieve higher performance improvements through supplier development (i.e. quality and flexibility) and distribution strategy (i.e. lead-time, quality, and delivery). The study will b helpful for policymakers, researchers, and practitioners in understanding the issues related to supply chain improvement planning, global configuration of supply chain and supply chain performance.